(untitled) (Research, Society and Development, 2021)
The present study aims to present current and relevant information about the closed treatment of isolated nasal fractures in adults, concerning the area of ​​surgery and oral-maxillofacial traumatology. To this end, a bibliographic survey of complete works published in English, Spanish or Portuguese, from January 2015 to September 2020, was carried out in the MEDLINE, LILACS, and BBO databases. After conducting the search and applying the inclusion and exclusion criteria, a sample of 12 articles was obtained, whose information was discussed in 3 different categories, according to their respective subjects. Given this study, it was observed that several studies have been carried out, to facilitate the management and improve the results in closed reductions of isolated nasal fractures in adults. Thus, it is up to the oral and maxillofacial surgeon to make use of current information present in the literature, aiming to abandon obsolete practices and provide a more satisfactory experience to patients.